Approaches to Description of the Composition and Properties of Vacuum Gas Oil for Constructing Mathematical Models of Deep Oil-Refining Processes; Theoretical Foundations of Chemical Engineering; Vol. 58, iss. 5 - Ivashkina E. N. Elena Nikolaevna; Nazarova G. Yu. Galina Yurievna; Dementjev A. Yu. Aleksandr Yurjevich; Sladkov D. Yu. Denis Yurjevich; Samoylov E. R. Evgeny Romanovich; Grigorash M. S. Mikhail Stepanovich (2024, 2024)
This paper presents the results of determining the composition of vacuum gas oil, a raw material for deep oil-refining processes, using two-dimensional gas chromatography. These results are the basis for describing the formalized mechanism of hydrocarbon transformations of high-boiling oil fractions in the processes of hydrocracking and catalytic cracking. The found hydrocarbon composition is used in modeling the composition of vacuum gas oil using the structure-oriented lumping method. The increment vectors of hydrocarbons contained in vacuum gas oil are compiled. The normal boiling point of the fraction is calculated for these vectors. Using the developed algorithm, the component composition of the raw material of the second stage of hydrocracking is reconstructed, according to which its fractional composition is calculated; the calculation error does not exceed 4°C. Based on laboratory and numerical studies, the reaction schemes of the processes of hydrocracking and catalytic cracking of vacuum gas oil are compiled. The studies performed using a mathematical model of cracking show that the involvement in the processing of mixed raw materials containing 15% distillate slack and 15% extract of selective oil purification allows increasing the productivity of the catalytic cracking unit and provides a favorable fuel mode for its operation